Assessing the impact of deviations in optimized multistep flow synthesis on the scale-up (vol 5, pg 838, 2020) - Sharma, M. K.; Raval, J.; Ahn, Gwang-Noh; Kim, Dong-Pyo; Kulkarni, A. A. (Reaction Chemistry & Engineering, 2021)

Assessment of a multipoint dosing approach for exothermic nitration in CSTRs in series - Mule, G. M.; Kulkarni, S.; Kulkarni, A. A. (Reaction Chemistry & Engineering, 2022)
The exothermic aromatic nitration of a biaryl compound is studied using various configurations of CSTRs in series. The relative rates of heat generation and heat removal in different configurations are compared to identify safer options while taking scale-up-related decisions. The effects of different parameters on the steady-state temperatures of the CSTRs are demonstrated through simulations. The use of multipoint dosing in three different CSTRs of increasing volume in series was compared with the use of standard CSTRs of equal volume in series. The distribution of the nitrating agent in three different CSTRs in series helped to distribute the heat duty and thereby helped maximise the throughput almost 2.4-fold when compared with a conventional approach based on the co-addition of all the reactants in the first CSTR. Various feed combinations were studied, and suitable designs that fall within the safe operating range of CSTRs for highly exothermic reactions are given.